(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
Within the framework of the PhD program in Physical Education at the University of Antioquia, with an emphasis on Sports Training, the possibility was proposed to work on a doctoral thesis topic: “Sports Training Planning through Modeling” (Agudelo, 2012) in team sports. The aim of this article is to clarify the evolution of a methodological route that highlights important considerations when selecting a research topic for a doctoral thesis in the field of sports training. After an exhaustive review of the scientific literature on planning (Afonso et al., 2020; Cunanan et al., 2018; Fisher & Csapo, 2021; González Ravé, 2021; Hammert et al., 2021; Hornsby et al., 2020; Junior, 2020; Kataoka et al., 2021; Kiely, 2010, 2018; Kiely et al., 2015; Loturco & Nakamura, 2016; Matomäki & Räntilä, 2021; Stone et al., 2021; Wackerhage & Schoenfeld, 2021), in English and from 2010 to 2021, it was concluded that the topic is less defined than expected, as significant academic contradictions were found both in terminology used to define and differentiate: programming, periodization, and planning (P-P-P) of sports training, and in the foundations that support these processes. In this context, it was decided to consider planning through Modeling in team sports as a possible general line of research for the PhD program, rather than as the topic of a single thesis. For this specific case, the focus was placed only on the P-P-P of Rugby, specifically for the Colombian national senior teams, known as the Tucanes. This research process is approached through an integrated multimethod design, specifically an iterative design (Polit DF & Hungler BP, 2000), with three fundamental stages: A qualitative hermeneutic stage (Edgar, 2013) to understand the reality of P-P-P processes in Colombian national rugby teams, for both men’s and women’s teams, from the perspective of coaches. A quantitative stage using the Delphi method (García-Ruiz & Lena-Acebo, 2018), which allows reaching expert consensus on P-P-P principles in Rugby. A randomized controlled trial (Moher et al., 2010) to measure both sports performance and physiological effects of a plan developed through Modeling, applied according to the results of the second stage. It is therefore concluded that, for an initial thesis idea, it is very important to start with a robust research topic that allows for defining a path that can later become much more concrete or specific. This is what happened with this initial thesis idea, which went from aiming to develop a model for all team sports to focusing on a specific methodological route, using an iterative methodology in a single sport—in this case, Rugby.